KOLABORASI DALAM PENGEMBANGAN OBJEK WISATA NEGERI DI ATAS AWAN (LOLAI) KABUPATEN TORAJA UTARA - H, Herman; Iva, Muhammad Irvan Nur Iva; Asripan, Andi Asripan; Pasae, Sri Devita Pasae; Has, Nur Izzatunnisa Has; Adawiyah, Putri Rabiah El Adawiyah; Ilyas, Putri Amalia Ilyas (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Collaboration between actors in the process of developing tourist attractions often does not go well. The main issue in this study is how the government builds good relations with the private sector and the community in developing the Lolai tourist attractions. This study aims to analyze the form of collaboration in the development of tourist attractions in the Land of the Clouds (Lolai) in North Toraja Regency. This type of research is qualitative and descriptive, aiming to describe the phenomenon that occurs. Data was collected through direct interviews with employees of the North Toraja Regency Tourism Office, tourist attraction managers, the community around the tourist attraction, as well as tourists, field observations, and documentation by collecting documents either in the form of writings, pictures, literature, or readings related to the research topic. The results of the study show that the existing collaboration is still in the early stages where face-to-face dialogue has not been optimally conducted, the level of trust between parties has not been formed, the government's commitment is strong but in its implementation is still weak, mutual understanding has begun to form but there are still differences in priorities, and provisional results show an increase as evidenced by the increase in tourist visits and the existence of community initiatives in the preservation of objects Lolai. For this reason, the government needs to strengthen participatory collaborative mechanisms by establishing regular communication forums between the government, the private sector, in this case tourist attraction managers, and the community.